Gastrointestinal Symptoms and Irritable Bowel Syndrome Are Associated With Female Sex and Smoking in the General Population and With Unemployment in Men - Nilsson, Daniel; Ohlsson, Bodil (Frontiers in Medicine, 2021)
Background: The influence of daily life exposure on the gastrointestinal tract is not fully understood. This study aimed to examine associations between functional gastrointestinal symptoms and sociodemographic status and lifestyle habits in the general population. Methods: The Malmö Offspring Study (MOS) included 2648 participants from the general population who had answered a questionnaire about sociodemographic status, lifestyle habits, medical health, and self-reported IBS. The visual analog scale for irritable bowel syndrome (IBS) was completed to assess gastrointestinal symptoms the past 2 weeks. Subjects with organic gastrointestinal diseases were excluded. Presence of self-reported IBS and gastrointestinal symptoms the past 2 weeks were used as dependent variables to study the associations with age, sex, body mass index, education, occupation, marital status, smoking, snuff using, alcohol drinking frequency, alcohol amount per drinking occasion, physical activity at work, and physical activity during leisure time, using logistic regression. Results: Self-reported IBS was associated with gastrointestinal symptoms the past 2 weeks (p<0.001). There was a positive association between IBS and female sex (p < 0.001), former smoking (p<0.001), present smoking (p<0.001), and an inverse association with drinking frequency of 2–3 times a week (p=0.051) and drinking 3-4 standard glasses per occasion (p=0.038). Gastrointestinal symptoms the past 2 weeks was associated with female sex (p<0.001), former smoking (p=0.001), and present smoking (p=0.012), whereas it was inversely associated with drinking 2-3 times/week (p=0.020) and ≥ 4 times/week (p=0.014). In men, IBS was associated with middle-age and both IBS and gastrointestinal symptoms were associated with unemployment (p<0.001 and p=0.001, respectively). In women, IBS was associated with present smoking (p=0.022), and gastrointestinal symptoms was associated with former smoking and inversely associated with higher age (p=0.006) and intermediate physical activity at work (p=0.008). IBS and gastrointestinal symptoms were not associated with BMI, education, marital status, or snuff using. Conclusion: Functional gastrointestinal symptoms in the general population shows strongest association with female sex and smoking, and inverse association with moderate alcohol drinking. In men, middle-age and unemployment is associated with gastrointestinal symptoms, whereas smoking is associated with symptoms in women.